In Vitro Evaluation of Surface Roughness and Bacterial Adhesion on Different CAD/CAM Restorative Materials - S. Ramesh Raja; Anarasi Mahaprasad; Sukanta K. Satapathy; Rishikesh K. Meshram; Syed N. Basheer; Sitansu S. Das; Mariea Francis (Journal of Pharmacy and Bioallied Sciences)
Introduction: This work sought to evaluate bacterial adherence to computer-aided design/computer-aided manufacturing (CAD/CAM) materials in relation to surface roughness and material type. Materials and Methods: We investigated four CAD/CAM restorative materials: hybrid ceramic, resin nano-ceramic, lithium disilicate, and zirconia. Surface roughness was determined with a profilometer. We assessed bacterial adhesion under a confocal laser microscope. Variations in surface roughness among independent groups were evaluated using the Kruskal-Wallis test. Results: The main result shows that surface roughness changed greatly among the groups. Conclusion: For CAD/CAM restorations, the smoothness of surfaces is absolutely important since plaque development and the transfer of allergenic compounds to these restorations surpass those of normal tooth surfaces.